Foliar fertilizer and irrigation effects on mung bean: implications for leaf physiology and yield - Han, Mengjie; Chen, Renqiang; Gao, Tongguo; Gao, Huiyan; Wang, Xiaoling; Liu, Meng; Lv, Tiebing; Zhu, Baoliang; Duan, Huike; Liu, Hongquan (Frontiers in Plant Science, 2025)
Addressing the growing demand for food in semi-arid regions requires effective water and fertilizer strategies. An irrigation and foliar fertilization field experiment was performed in Baoding, Hebei Province, to determine the effects of foliar nutrition and water conditions on mung bean (Vigna radiata L.), with focus on leaf traits, photosynthetic characteristics, and yield. The treatments were irrigated at branching and flowering-podding stages. Foliar treatments were freshwater only, high-potassium, high-phosphorus, balanced fertilizer. The two-factor experiment comprised a total of eight treatments and twenty-four plots which were arranged randomly. Numerous parameters, including leaf traits, photosynthetic parameters, SPAD dynamics, and yield components, were determined. Results showed that under full irrigation, the high- phosphorus treatment (W1F2) significantly enhanced leaf area, net photosynthetic rate (Pn), and SPAD values by 18.1%, 14.4%, and 24.0%, respectively, at 7 days after spraying (DAS7), and delayed leaf senescence. Under water stress, the balanced fertilizer (W0F3) most effectively mitigated stress effects, showing the smallest reduction in leaf area and a 9.8% higher SPAD retention. Photosynthetic performance varied: W1F2 maintained the highest water use efficiency over 21 days under full irrigation, while W0F3 showed the least decline in Pn under water stress. Yield increased significantly with high- phosphorus treatment (F2), by 30.86% (under W1 conditions) and 37.79% (under W0 conditions), primarily due to a 20.66% and 19.17% rise in grains per pod, respectively. The W0F3 treatment also increased 100-seed weight by 8.12%, supporting yield advantage. In conclusion, high- phosphorus foliar fertilizer is recommended under sufficient irrigation to boost photosynthesis and sink strength, whereas the balanced fertilizer provides yield advantages under water-limited conditions by maintaining photosynthetic area and grain weight. This study provides a theoretical and practical foundation for precision foliar nutrient management in mung beans during the flowering and podding stages in semi-arid regions.